Clinical Weakness Predicts Malignancy in Patients With Peripheral Nerve Sheath Tumors. (16th November 2020) - Pendleton, Courtney; Zheng, Clark; Murthy, Nikhil; Spinner, Robert J
Abstract: INTRODUCTION: Both benign and malignant peripheral nerve sheath tumors (PNST) may arise spontaneously, in conjunction with tumor-forming syndromes, or in previously radiated patients. Distinguishing benign from malignant PNST may be challenging. METHODS: We reviewed the electronic records for patients with benign peripheral nerve sheath tumors (BPNST) and those with MPNST. Data regarding the involved nerve(s), presence and magnitude of weakness were collected. Tumors involving cranial nerves or with spinal cord compression were excluded. The MRC scale was used to grade weakness (averages were calculated and rounded to the nearest valid MRC score). RESULTS: There were 718 benign PNST of motor nerves (603 schwannoma, 115 neurofibroma) and 126 MPNST of motor nerves. For schwannomas, 38/603 had clinical weakness at presentation (6.3%). The average MRC score was 4.5 (range 2-4 +, stdev 0.55). Only one patient had an MRC < 3, and this patient had a schwannoma within Guyon's canal causing compression of the nerve. For neurofibromas, 19/115 had clinical weakness at presentation (16.5%). The average MRC score was 4 (range 1-4 +, stdev 0.88). Only plexiform neurofibromas had an MRC < 3. Eleven plexiform neuromas had clinical weakness; this included five neurofibroma chains along a single nerve, and six solitary plexiform neurofibromas. The average length of the solitary plexiform tumors was 7.74 cm (range: 3.2-12 cm). When plexiform tumors were excluded, the average MRC score was 4 (range 4 − -4 +, stdev 0.177). For MPNSTs, 54/126 had clinical weakness at presentation (42.9%). The average MRC score was 2 (range 0–4, stdev 1.51). There was a significant difference between the average MRC in patients with schwannomas versus MPNST (p < 0.0001), as well as between patients with neurofibromas versus MPNST (p < 0.0001). CONCLUSION: MPNST had significantly lower MRC scores than benign PNST. An MRC < 3 was see almost exclusively in MPNSTs. Conveniently, an MRC 3 has an easily reproducible clinical definition. In the absence of a plexiform tumor, or a tumor compressing a nerve (i.e., within a canal or tunnel) a clinical exam demonstrating less than antigravity strength should prompt serious consideration of a MPNST.